Risks and Opportunities in Post-Covid-19 Resilience Programs - Emilia Cornelia STOICA; Liviu RADU (Communications of International Proceedings, 2021)
The term resilience shows the resistance of a system – natural environment, economic, social - to shocks or stressors. Resilience can be determined using some indicators that describe the characteristics of the analyzed system, as well as of disruptive events. At the same time, the results of this approach will be used in medium and long-term development strategies, and the policies considered appropriate for the implementation of these strategies will use techniques and mechanisms that take into account the specifics of risks, including of the identified resilience process. Although combating the crises facing society, as well as the actual elaboration of resilience, recovery and resumption of economic and social growth programs are costly actions, they can be considered opportunities for future development.
Keywords: COVID 19 crisis; resilience; vulnerability